2010
DOI: 10.1163/187847510x490826
|View full text |Cite
|
Sign up to set email alerts
|

Where's the Floor?

Abstract: Visual and balance cues concerning the relative orientation of ourselves and our environment combine to direct our steps to select a secure footing. How are visual cues used to select the best support surface? Here we show that, when exposed to tilted, rectangular rooms of various aspect ratios, subjects do not necessarily choose the surface with its normal oriented closest to the gravity-defined vertical. Rather their decision is also strongly biased by the visual area subtended by each candidate surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…A public domain photography of the interior of the Harmony ISS module 1 was used as visual context for all tasks (see Figure 1, panel B). This photograph was chosen because it provides photo-realistic orientation visual cues, in the form of a structural rectangular frame (a chief factor in determining the orientation of the visual context; see Harris et al, 2010, 2011), which are nonetheless invariant when the picture is flipped either horizontally or vertically (allowing an experimental control of eventual salient visual features that might serve as a landmark for the spatial localization task; see Hubbard & Ruppel, 1999). Furthermore, this scene provides a reasonable analogue of the visual cues available in microgravity environments, supporting tentative links between our results and applied settings for human factors considerations.…”
Section: Methodsmentioning
confidence: 99%
“…A public domain photography of the interior of the Harmony ISS module 1 was used as visual context for all tasks (see Figure 1, panel B). This photograph was chosen because it provides photo-realistic orientation visual cues, in the form of a structural rectangular frame (a chief factor in determining the orientation of the visual context; see Harris et al, 2010, 2011), which are nonetheless invariant when the picture is flipped either horizontally or vertically (allowing an experimental control of eventual salient visual features that might serve as a landmark for the spatial localization task; see Hubbard & Ruppel, 1999). Furthermore, this scene provides a reasonable analogue of the visual cues available in microgravity environments, supporting tentative links between our results and applied settings for human factors considerations.…”
Section: Methodsmentioning
confidence: 99%
“…In conclusion, the present study successfully extended the previous finding that the orientation of Representational Horizon, indexed by the second harmonic component underlying the patterns of spatial localisation of a moving target, is biased by visual orientation cues (Freitas & De Sá Teixeira, 2021 ). Specifically, this biasing was found to be reliably induced by a variety of natural scenes, further emphasising the link between dynamic representations of motion (Freyd, 1987 ; Hubbard, 2005 , 2010 , 2015 ), internal models (De Sá Teixeira & Hecht, 2014 ; De Sá Teixeira et al, 2013 , 2019a , b ; Lacquaniti et al, 2013 ; McIntyre et al, 2001 ), and spatial orientation (Haji-Khamneh & Harris, 2010 ; Harris et al, 2011 ; Howard & Templeton, 1973 ; Jenkin et al, 2010 , 2011 ; MacNeilage et al, 2008 ; Mittelstaedt, 1986 ).…”
Section: Discussionmentioning
confidence: 99%
“…The second harmonic’s orientation was found to be biased towards the horizon implied by the visual context—that is, targets moving along the horizontal line implied by the background scene (irrespective of its misalignment with the actual horizontal) led to increased M-displacements. This trend was further found to be correlated, at an individual level, with measures of subjective visual vertical (SVV) made with the same visual context, strengthening the relevance of visual spatial orientation (Haji-Khamneh & Harris, 2010 ; Harris et al, 2011 ; Howard & Templeton, 1973 ; Jenkin et al, 2010 , 2011 ; MacNeilage et al, 2008 ; Oman, 2007 ) for the perception of dynamic events (see also Moscatelli & Lacquaniti, 2011 ).…”
mentioning
confidence: 82%
“…One possible explanation for the horizon effect is the aspect ratio of the room. Harris, Jenkin, Jenkin, Dyde, and Oman (2010) reported that when participants chose a surface to stand on among the surrounding walls of a tilted room, the choice probability of each surface depended on the retinal area of each wall. As the room in the present study was rectangular, the floor and ceiling occupied larger retinal areas than the walls, and so might have been more relevant as the supporting surface than the walls, thus serving as implicit horizon cues.…”
Section: Discussionmentioning
confidence: 99%